Double β Decay and the Axial Strength - Suhonen, Jouni; Kostensalo, Joel (Frontiers in Physics, 2019)
Quenching of the weak axial strength gA is discussed and relations of this quenching to the nuclear matrix elements of double beta decays are highlighted. An analysis of Gamow-Teller transitions in the mass range A = 62 − 142 is presented and its results are compared with those of many previous works. The enhancement of the axial charge is discussed for first-forbidden pseudoscalar β transitions. Higher-forbidden β transitions are introduced and their role in determining the effective value of gA is examined, in particular from the point of view of the β-decay half-lives and the shapes of electron spectra of forbidden non-unique β transitions.